Three-Territory DWI Acute Infarcts: Diagnostic Value in Cancer-Associated Hypercoagulation Stroke (Trousseau Syndrome) - Finelli, P.F.; Nouh, A. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: DWI infarcts involving the bilateral anterior and posterior circulation suggest an embolic etiology. In the absence of an identifiable embolic source, we analyzed DWI lesions involving these 3 cerebral territories to determine the diagnostic value for ischemic infarction caused by cancer-associated hypercoagulation.MATERIALS AND METHODS: A retrospective analysis of all brain MR imaging studies at our institution from July 2014 to June 2015 was conducted, yielding 4075 studies. Of those, 17% (n = 709) contained the terms “restricted-diffusion” plus either “numerous,” “innumerable,” “multiple,” or “bilateral.” Of these 709 reports, 6% (n = 41) of DWI lesions involving 3 or more vascular territories of the bilateral anterior and posterior circulation were analyzed.RESULTS: Of the 41 patients, 19 separate etiologies were identified, the most frequent being malignancy-related infarctions (22% [n = 9]) and hypoxic-ischemic injury (12% [n = 5]). Only 2 patients had an indeterminate etiology. The most frequent etiology of infarctions not suspected clinically or radiographically was malignancy (P < .001). Infarctions of malignancy had a characteristic appearance, being nonenhancing, nonring-appearing clusters or single areas of restricted diffusion of 0.5–2 cm with a peripheral location or larger vascular territories, uncommonly in a watershed distribution, and with absence of diffuse cortical ribbon or deep gray nuclei involvement.CONCLUSIONS: Approximately 1 in 5 ischemic infarcts in patients with DWI lesions involving 3 vessel territories are malignancy related. In the absence of an identifiable embolic source, ischemic infarction with cancer-associated hypercoagulation accounts for 75% of cases. Cancer-associated hypercoagulation infarction should be considered, particularly when no other cause is apparent.TSTrousseau syndrome